The Influence of Learning Models Cooperative Type Numbered Heads Together (NHT) on Learning Outcomes of Mathematics Students SMP Muhammadiyah 01 Medan - Dahlianasari Syahputri; Rusydi Ananda (MASI Mandiri Edukasi, 2025)
This study aims to address the low mathematics learning outcomes of eighth-grade students in flat-sided shapes lessons by applying the NHT learning model. The method used is quantitative with a quasi-experimental approach. Sampling was conducted using cluster random sampling from SMP Muhammadiyah 01 Medan. The research design used was a control group. The research instruments were pretest and posttest essay questions. The results showed that the experimental class obtained a higher average N-Gain score of 0.790 (high category) compared to the control class, which obtained a lower average N-Gain score of 0.445 (medium category). The hypothesis test results from the N-Gain data yielded a t-count of 6.025, which is greater than the t-table value of 1.668 at a significance level of 0.05. Therefore, it can be stated that Ha is accepted. These findings suggest that the application of the NHT model significantly enhances students' mathematics learning outcomes. This suggests that cooperative learning, supported by the NHT model, can be an effective alternative for encouraging more active, collaborative, and meaningful mathematics learning in junior high schools.